VOC and O3 distributions over the Densely populated area of Greater Athens, Greece - Flocas, H.A.a; Assimakopoulos, V.D.a; Helmis, C.G.a; Güsten, H.b (Journal of Applied Meteorology, 2003)
The horizontal and vertical distributions of volatile organic compounds (VOCs) and ozone (O3) concentrations within the lower troposphere over the greater Athens area. Greece, under sea-breeze conditions were studied. Furthermore, an attempt was made to explain the dynamic and chemical mechanisms responsible for the formation of these distributions. Measurements were collected using a specially instrumented Falcon 20-E5 research aircraft, ground-based meteorological instrumentation, and a network of air quality monitoring stations within the context of the Scientific Training and Access to Aircraft for Atmospheric Research Throughout Europe (STAAARTE) 1997 experimental campaign. Relatively high ozone values (55-100 ppbv) were identified within the first 300-400 m above ground, and significantly reduced values were found over the depth of the atmospheric boundary layer. High values of VOC concentrations [150-350 ppbCarbon (C)] were observed near the ground as well as within the first 300 400 m above ground. At higher altitudes, of 1400-1600 m, VOC concentrations remained relatively high (100-200 ppbC). It was demonstrated that the sea-breeze circulation plays a major role in the formation of the above-mentioned concentration levels and that chemical transformations explain specific characteristics.
Keywords: Athens [Attica]; atmospheric pollution; Boundary layers; Chemical transformations; Meteorology; Ozone; Population statistics; troposphere; urban pollution; volatile organic compound; Volatile Organic Compounds